2018
DOI: 10.1016/j.bja.2018.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal handshake technique in locating the cricothyroid membrane: a non-randomised comparative study

Abstract: Background: Evaluation of the anterior neck anatomy is used to identify the cricothyroid membrane (CTM) before front of neck airway access. This has been traditionally performed using palpation which results in misidentification of the CTM in a high proportion of subjects. The 'laryngeal handshake' is currently advocated by the Difficult Airway Society as the method to identify the CTM. We sought to investigate the accuracy of this technique in females. Methods: Five clinicians were asked to identify the CTM u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…8,24 Although the study designs are different, the accuracy rates reported with the i-gel ® in place are similar to that with the laryngeal handshake technique (66% vs 62%). 25 Combined, these studies reflect the fact that although optimising technique may increase success rates, palpation alone does not seem to result in accuracy rates of more than two-thirds in females, and although palpation techniques are pragmatic they are distinctly inferior to focused airway ultrasound in terms of accuracy.…”
Section: Discussionmentioning
confidence: 82%
“…8,24 Although the study designs are different, the accuracy rates reported with the i-gel ® in place are similar to that with the laryngeal handshake technique (66% vs 62%). 25 Combined, these studies reflect the fact that although optimising technique may increase success rates, palpation alone does not seem to result in accuracy rates of more than two-thirds in females, and although palpation techniques are pragmatic they are distinctly inferior to focused airway ultrasound in terms of accuracy.…”
Section: Discussionmentioning
confidence: 82%
“…The middle finger and thumb are made to rest on the cricoid cartilage, and the index finger is used for palpating the CTM (Frerk et al, ). Moreover, the laryngeal handshake method has been shown to result in a higher CTM identification rate (62%) than the conventional method (33%; Drew & AcCaul, ). For this reason, it seems better to teach students this method in future.…”
Section: Discussionmentioning
confidence: 99%
“…The management of CICO scenario is a critical time and delayed or failed emergency cricothyroidotomy leads to acute cerebral hypoxia and death [16].…”
Section: Neoplastic Laryngo-hypopharyngeal Obstructionsmentioning
confidence: 99%
“…As reported by this author, the maneuver is performed with the thumb and the middle finger of the dominant hand identifying the hyoid and thyroid laminae, stabilizing the larynx between these two fingers, and moving down the neck to palpate the cricothyroid membrane with the index finger. After that the index finger of the dominant hand is substituted by that of the non-dominant hand and the dominant hand stabilized on the sternum is used to make the procedure [16,34].…”
Section: Surface and Surgical Anatomymentioning
confidence: 99%